1999
DOI: 10.1021/om990254x
|View full text |Cite
|
Sign up to set email alerts
|

Coordination and Rearrangement of Organic Chalcogenides on a Rhodium−Rhodium Bond:  Reactions with Strained-Ring Cyclic Thioethers and with Selenium and Tellurium Ligands

Abstract: When the cyclic thioethers L = and were added to [(η5-C5H5)2Rh2(μ-CO)(μ-η2:η2-CF3C2CF3)] (1), the coordinative addition products [(η5-C5H5)2Rh2(CO)(μ-η1:η1-CF3C2CF3)L] (2a−c) were formed reversibly. When it is left in solution in the presence of excess ligand, the propylene sulfide complex 2b (L = transforms to the bridging sulfido complex [(η5-C5H5)2Rh2{μ-η1:η1:η2-C(O)C(CF3)C(CF3)}(μ-S)] (3a). A similar reaction occurred, but to a lesser extent, with the trimethylene sulfide complex 2a (L = Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The reaction of TeR 2 (R ¼ Me, Et) with metallocyclic [(C 5 H 5 ) 2 Rh 2 (m-CO)(CF 3 CCF 3 )] derived an adduct in which TeR 2 was added to one of the rhodiums attached with bridging carbonyl, which was boned in a h 1 fashion. 69 Such a type of insertion followed by the addition of tellurium can be particularized due to diffusive sets of lone pairs and their ease of availability to coordination. While the reaction of RhCl The uxional behavior of the latter complex was established by its 1 H NMR spectrum, which showed a single resonance for TeMe, CH 2 , and COD (Scheme 3).…”
Section: Rhodium and Iridiummentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of TeR 2 (R ¼ Me, Et) with metallocyclic [(C 5 H 5 ) 2 Rh 2 (m-CO)(CF 3 CCF 3 )] derived an adduct in which TeR 2 was added to one of the rhodiums attached with bridging carbonyl, which was boned in a h 1 fashion. 69 Such a type of insertion followed by the addition of tellurium can be particularized due to diffusive sets of lone pairs and their ease of availability to coordination. While the reaction of RhCl The uxional behavior of the latter complex was established by its 1 H NMR spectrum, which showed a single resonance for TeMe, CH 2 , and COD (Scheme 3).…”
Section: Rhodium and Iridiummentioning
confidence: 99%
“…Compared to other platinoids, a signicant amount of work has been documented on Pd(II) and Pt(II) complexes derived from telluroethers. [65][66][67][68][69] Among these cyclic complexes, [MX 2 {Te(CH 2 ) 4 } 2 ] (M ¼ Pd, Pt; X ¼ Cl, Br, I) has been isolated from the reaction with cyclic telluroethers, i.e., telluracyclopentane Te(CH 2 ) 4 . 72 In the case of the platinum metal system, both cis-and trans-congured complexes have been reported.…”
Section: Palladium and Platinummentioning
confidence: 99%
“…Previously, we have shown that the reaction of dialkyl sulfides, SRRЈ to [(η-C 5 H 5 ) 2 Rh 2 (μ-CO)(μ-η 2 :η 2 -C 2 (CF 3 ) 2 )] (1) proceeded by coordination of the sulfide [19,20] and giving [(η-C 5 H 5 ) 2 Rh 2 (μ-CO)(μη 1 :η 1 -C 2 (CF 3 ) 2 )(SRRЈ)], a reaction which was reversible. On prolonged contact with SR 2 (R ϭ Me, Et) interesting transformations occurred, giving [(η-C 5 H 5 ) 2 Similarly reaction of 1 with a strained cyclic thio-, selenoand telluro-ether compounds gave the addition products (analogous to 2) reversibly in the first instance [18], but work-up of solutions containing excess cyclochalcoether gave complexes 5. These complexes can also be prepared by the reaction of the elements [18] with 1; in the case of elemental Se another isomer 6 was isolated, the structure sharing a similarity with complexes 4.…”
Section: Structure Determination Of 4dmentioning
confidence: 99%
“…On prolonged contact with SR 2 (R ϭ Me, Et) interesting transformations occurred, giving [(η-C 5 H 5 ) 2 Similarly reaction of 1 with a strained cyclic thio-, selenoand telluro-ether compounds gave the addition products (analogous to 2) reversibly in the first instance [18], but work-up of solutions containing excess cyclochalcoether gave complexes 5. These complexes can also be prepared by the reaction of the elements [18] with 1; in the case of elemental Se another isomer 6 was isolated, the structure sharing a similarity with complexes 4.…”
Section: Structure Determination Of 4dmentioning
confidence: 99%
“…Of the few known crystal structures of mononuclear rhodium complexes that contain telluroether ligands [9][10][11][12][13], [RhCp * L][PF 6 ] 2 {L = MeS(CH 2 ) 3 Te((CH 2 ) 3 SMe)} is of special interest, since L acts as a tridentate ligand with one Te and two S donor atoms [13]. To our knowledge, no crystal structures of such hybrid rhodium complexes containing discrete thioether and telluroether ligands have hitherto been reported.…”
Section: Introductionmentioning
confidence: 99%